OBLICZA MULTIKULTURALIZMU POGRANICZA (NATALKA BABINA, MIASTO RYB) - Zywert, Aleksandra (Acta Neophilologica, 2018)
The novel The Town of Fish (Рыбiн горад, 2007) by Natalia Babina is an extraordinary work within contemporary Belarusian literature due to both its content and formal characteristics. It is an eclectic text, which includes elements of the action and detective novel, fantasy, the novel of manners, and even the reportage. The story of the main character is a mere pretext for contemplating some aspects and condition of modern Belarus as well as identity issues of its inhabitants (especially from the borderland). In this context, Babina’s novel, despite its fantastic and entertaining layers, is a significant voice in the discussion concerning the dimensions of modern multiculturalism devoid of “divisions into majorities and minorities, the familiar and the other, the better and the worse”.